Effect of CO-SCR by CTAB modified vanadosilicate molecular sieve on low temperature catalytic denitrification - HE Han-bing; FU Guo-you; ZHANG Li; ZENG Jing; WANG Yu-si; LONG Hong-ming; FAN You-qi; ZHENG Ya-jie; MA Ying (Cailiao gongcheng, 2021)
To improve the NO-CO low-temperature selective catalytic reduction (SCR) denitration rate, finding new effective denitration catalysts has become the focus of the denitration field. A vanadium-substituted molecular sieve AM-6 was synthesized by hydrothermal method, the performance of AM-6 molecular sieve was improved by surfactant-assisted synthesis. The effect of different amounts of CTAB on the morphology, composition and the catalytic reduction performance was studied. These catalysts were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). The results show that the addition of CTAB does not introduce other impurity elements. When the ratio of CTAB to V is 1:4, AM-6(1/4CTAB) has more regular surface morphology, better crystalline formability, well-balanced ratio of V5+/V4+, and the denitrification activity reaches 81.54% at 150℃, which is reduced by 50℃ than the temperature at which the denitrification activity of AM-6 reaches 80%.